2013
DOI: 10.1007/s10484-013-9230-9
|View full text |Cite|
|
Sign up to set email alerts
|

Negative Mood and Alcohol Problems are Related to Respiratory Dynamics in Young Adults

Abstract: This study examined the relationship of negative affect and alcohol use behaviors to baseline respiration and respiratory response to emotional challenge in young adults (N = 138, 48% women). Thoracic-to-abdominal ratio, respiratory frequency and variability, and minute volume ventilation (MVV) were measured during a low-demand baseline task, and emotional challenge (viewing emotionally-valenced, emotionally-neutral, and alcohol-related pictures). Negative Mood and Alcohol Problems principal components were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…The transition of drug addicts from occasional to compulsive drug use and the failure to stop drug use leading to frequent relapse are the key issues in drug addiction 1 . It has been confirmed that drug‐related contexts 2 or emotional mood 3 can trigger relapse. Attentional bias toward addiction‐related cues is a central factor in addiction and its related problems 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The transition of drug addicts from occasional to compulsive drug use and the failure to stop drug use leading to frequent relapse are the key issues in drug addiction 1 . It has been confirmed that drug‐related contexts 2 or emotional mood 3 can trigger relapse. Attentional bias toward addiction‐related cues is a central factor in addiction and its related problems 4 .…”
Section: Introductionmentioning
confidence: 99%